Synthesis and Characterization Materials Modern (CMC-Fe3O4-Chitosan-TiO2) As Portable Adsorbent Toxic Metal (Hg) and Dye Substance (Rh B) - Kaharuddin Kahar; Muh Edihar; Suhardin (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
The synthesis of the portable adsorbent material CMC-Fe3O4-Chitosan-TiO2 begins by inserting the CMC-Chitosan mixture into the leaching solution. Next, concentrated NaOH and 3% CaCl2 were added, then decanted and dried at room temperature. After that, the composite was coated with TiO2 and then dried in an oven at a temperature below 100 oC. The success of the synthesis was indicated by the presence of specific absorption in FT-IR. 3429 cm-1 hydroxyl group, 2926 cm-1 for the CH/CH3 group, 1631 cm-1 for the carbonyl group (C=O), 1642 cm-1 which is the CH/CH3 group, as well as ) and ( at 400-600 cm-1. In addition, the different surface morphology of the material formed from its basic components is based on SEM characterization sails. Adsorption test results for Hg (II) metal ions were 53% while dyes were 38% with a time of 40 minutes. This research is good for handling watermaster